Study of the Influence of Annealing Temperature on the Structural and Optical Properties of ZnTe Prepared by Vacuum Thermal Evaporation Technique - Ali, Sarmad M.; Shehab, Alia A.A.; Maki, Samir A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The ZnTe alloy was prepared as  deposited thin films on the glass substrates at a thickness of 400Â±20 nm using vacuum evaporation technique at pressure (1 Ã— 10-5) mbar and room temperature. Then the thin films under vacuum (2 Ã— 10-3 mbar) were annealing at (RT,100 and 300) Â°C for one hour. The structural properties were studied by using X-ray diffraction and AFM, the results show that the thin films had approached the single crystalline in the direction (111) as preferred orientation of the structure zinc-blende for cubic type, with small peaks of tellurium (Te) element for all prepared thin films. The calculated crystallite size (Cs) decreased with the increase in the annealing temperature, from (25) nm before the annealing to (21) nm after the annealing. The images of atomic force microscopy of all thin films appeared a homogenous structure and high smoothness through roughness values â€‹â€‹that increased slightly from (1.4) nm to (3.4) nm. The optical properties of the ZnTe at (RT,100 and 300) Â°C were studied transmittance and absorbance spectrum as a function of the wavelength. The energy gap was found about (2.4) eV for the thin films before the annealing and increased slightly to (2.5) eV after annealing at 300 Â°C